Construção de um biossensor potenciométrico impresso para determinação de adrenalina - Oliveira, Andressa Cristina Vasques De (2017)
Adrenaline is released into the blood by the sympathetic nervous system and the suprarenal medulla. It is of great importance for organisms acting from the prolongation of the effect of local anaesthetics to their action on the heart and can restore heart rate in the event of cardiac arrest. In this way, it presents itself as an important topic of study. On the other hand, paperbased biosensors, because they are a relatively simple technique, inexpensive and easily accessible, also have great potential as a tool for analytical chemistry. These utilize an enzyme that can catalyze an oxidation or reduction of the analyte and generate a signal proportional to the concentration thereof. As a biological element of the proposed biosensor, the enzyme Polyphenoloxidase was used. Therefore, in this work, a potentiometric biosensor for adrenaline determinations was constructed. The reference electrode was printed on parchment paper (Filipinho®) using an inkjet printer (Hp 2050®) with the original ink cartridges. The printing ink was modified with Potassium Chloride and Silver Nitrate. The indicator electrode was constructed from the printing of the conductive part, i.e., ink with KCl. The working electrode was obtained from the immobilization of the enzyme in paste form containing graphite and commercial jelly (Dr. Oetker®). The impression of both electrodes originated, therefore, the proposed biosensor. The enzyme was extracted from the yam (Colocasia sp.) With phosphate buffer (pH = 7.0). The best composition was 1000 μL of Enzymatic Crude Extract (EBE) with 500 μL of jelly and 0.330 g of graphite powder. The portable equipment, for potentiometric measurements, consists of a computer interface (Arduino Duo®) that has analogue inputs with 12-bit resolution. To adjust the input impedance, a circuit (Op-Amp CI OP07, Analog Devices®) of the buffer type was constructed. Communication with the user was done through a program developed in visual language Basic®; the interface was connected to the computer through the USB port. Employing Adrenaline solutions in phosphate buffer (pH = 7.0). The Detection Limit (LD = 2.15 x 10-4 mol L -1) was calculated and the linear response range was 5x 10-2 to 5x10-4 mol L -1. The accuracy was checked against a titration method, and the results were concordant at a 95% level (paired t-test). The system was applied for the determination of adrenaline in injectable drugs, and the results were satisfactory the precision expressed in coefficient of variation was always less than 22%.